2015
DOI: 10.3389/fonc.2015.00277
|View full text |Cite
|
Sign up to set email alerts
|

Human Papilloma Viruses and Breast Cancer

Abstract: PurposeHuman papillomaviruses (HPV) may have a role in some breast cancers. The purpose of this study is to fill important gaps in the evidence. These gaps are: (i) confirmation of the presence of high risk for cancer HPVs in breast cancers, (ii) evidence of HPV infections in benign breast tissues prior to the development of HPV-positive breast cancer in the same patients, (iii) evidence that HPVs are biologically active and not harmless passengers in breast cancer.MethodsRNA-seq data from The Cancer Genome At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 51 publications
9
52
1
8
Order By: Relevance
“…Although we have shown the presence of HR-HPV in benign specimens, we were unable to confirm the expression of the HR-HPV protein in theses samples. While we did not find evidence of viral expression in benign cases which were positive for HPV DNA, others were able to show the expression of HPV oncoprotein in benign samples via immunohistochemistry (IHC) method35. The most reasonable conclusion to draw from this is that that the low level of HPV expression could be detected mainly by IHC where the viral expression can be detected even if only in a few cells.…”
Section: Discussioncontrasting
confidence: 54%
“…Although we have shown the presence of HR-HPV in benign specimens, we were unable to confirm the expression of the HR-HPV protein in theses samples. While we did not find evidence of viral expression in benign cases which were positive for HPV DNA, others were able to show the expression of HPV oncoprotein in benign samples via immunohistochemistry (IHC) method35. The most reasonable conclusion to draw from this is that that the low level of HPV expression could be detected mainly by IHC where the viral expression can be detected even if only in a few cells.…”
Section: Discussioncontrasting
confidence: 54%
“…Lawson et al [43] observed “the presence of high-risk HPV gene sequences in breast cancers; that HPV oncogenic influences may occur early in the development of breast cancer; that HPVs in breast cancer are likely to be biologically active (as shown by transcription of HPV DNA to RNA plus the expression of HPV E7 proteins), and that there appeared to be a correlation between high-risk HPV in benign breast specimens and subsequent HPV-positive breast cancer in the same patient.” In another study, Subhawong et al [44] showed that basal-like breast carcinomas, which resemble HPV-associated squamous cell carcinomas morphologically, frequently exhibit a similar Rb − /p16 + phenotype. A study from Singapore showed a high prevalence of infection with high-risk HPV in breast cancer patients [45].…”
Section: Triple-negative Breast Carcinoma In East Asiansmentioning
confidence: 99%
“…The most іmportаnt risk factors are viral factors whіch аrе consіdеrеd іnfеctіous аgеnts of humаns аnd lіnkеd to thе іncіdеncе of cаncеr іn thе body. Studіеs hаvе shown thаt thе rаtе of 17-20% of cаsеs of cаncеr іs duе to а vіrаl іnfеctіon [5].Іn 1995, 21% of brеаst cаncеr sаmplеs wеrе tаkеn аnd ЕBV wаs dеtеctеd іn thе sаmplеs аftеr thе dіscovеry, sеvеrаl studіеs wеrе conductеd thаt showеd ЕBV іnϳury іn womеn wіth brеаst cаncеr [6]. Humаn cytomеgаlovіrus (HCMV) аnd Еpstеіn -Bаrr vіrus (ЕBV) could potеntіаlly іnvolvе іn brеаst cаncеr [7].…”
Section: Introductionmentioning
confidence: 99%